Zen Buddhism in Japanese poetry (Journal of Oriental Studies, 2017)
This article attempts to examine the impact of Zen-buddizm on Japanesepoetry.The definition of the concept of Zen-buddizm, its ideologicalprinciples. Reveals the origins of Zen -buddizm, its influence on Japaneseculture. Emphasis is placed on the reflection of the ideas of zen-buddhismin the creation of the famous Japanese poet Matsuo Basho as well as traditionalJapanese poetry haikai genre.